Preparation of MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation

By using tannin acid and 3-aminopropyltriethoxysilane in MXene membranes, the growth of hydrophilic nanoparticles was regulated, and the complexity and stability of MXene membrane spacing regulation was solved, and dye/ The efficient separation and high water permeability of salt are suitable for large-scale applications.

CN119258804APending Publication Date: 2025-01-07DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411566714.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing MXene membranes have harsh reaction conditions, complex process and poor stability when regulating layer spacing, making it difficult to achieve high selectivity and high water permeability of dyes/salts at the same time.

Method used

The chemical reaction of tannin acid and 3-aminopropyltriethoxysilane was carried out in the sub-nanospace of the MXene membrane. By regulating the reaction time and concentration, the growth of hydrophilic nanoparticles was controlled to achieve continuous regulation of layer spacing.

Benefits of technology

The MXene membrane is able to efficiently retain salt ions and dye separation, while maintaining high water permeability, mild reaction conditions, simple process, and good large-scale application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258804A_ABST
    Figure CN119258804A_ABST
Patent Text Reader

Abstract

The invention relates to preparation of an MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, and the MXene composite membrane for dye / salt separation is prepared by soaking an MXene membrane in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane at room temperature. The chemical reaction between tannic acid and 3-aminopropyltriethoxysilane is introduced into the sub-nano space of the two-dimensional MXene membrane for the first time, the interlayer spacing of the MXene membrane can be continuously regulated and controlled, the operation is simple and efficient, salt ions are intercepted by the MXene membrane, and dye / salt is efficiently separated, and meanwhile, high water permeability is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation and relates to the preparation of a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation. Background Art

[0002] Compared with other water treatment methods, membrane separation technology has the advantages of simple equipment, low energy consumption and high selectivity, and can achieve precise and continuous separation with high efficiency and low investment. In the membrane separation process of printing and dyeing wastewater in the textile industry, the solution passes through a porous membrane to remove dyes, salts, heavy metal ions and other solutes. Usually, dye molecules are separated from water due to their size or charge differences relative to the membrane. Generally speaking, larger dye molecules and ions with similar charges to the membrane are easily separated, while some salts such as NaCl and Na2SO4 can pass through the membrane. The core task of membrane separation technology is the development of membrane materials with specific separation functions. The increase in permeability of traditional separation membranes is often accompanied by a decrease in selectivity, and at the same time, they have short lifespans, poor thermal stability and corrosion resistance, etc.

[0003] As a new type of two-dimensional transition metal carbide / nitride, two-dimensional MXene has broad development space in water treatment applications. The surface of MXene is rich in hydrophilic functional groups such as -OH, -O, and -F, which makes it have good hydrophilicity and electronegativity. At the same time, compared with traditional organic membranes, this type of membrane is theoretically composed of nano-thick sheets, so the thickness can be controlled, and the size of the two-dimensional channels formed between the layers can be controlled, so it can show more stringent size screening characteristics. The membrane stacked by the sheet structure has a regular wrinkle-free transmission channel, allowing water molecules to pass quickly and stably in the membrane. Due to the size screening effect, impurities in the water can be removed by regulating its interlayer spacing. At the same time, the MXene membrane has excellent mechanical properties and flexibility.

[0004] At present, the methods for regulating the interlayer spacing of MXene membranes mainly include the following four methods: 1. High-temperature sintering to reduce the interlayer spacing (Reference 1: Adjustable interlayer spacing of ultrathin MXene-derived membranes for ion rejection [J]. Journal of Membrane Science 591, 117350 (2019).); 2. Blending with other substances for adjustment (Reference 2: Column-to-Beam Structure House Inspired MXene-Based Integrated Membrane with Stable Interlayer Spacing for Water Purification [J]. Advanced Functional Materials 32, 2111660 (2022).); 3. Alkali treatment (Reference 3: Balancing MXene Surface Termination and Interlayer Spacing Enables Superior Microwave Absorption [J]. Advanced Functional Materials 33, 2301449 (2023).); 4. Adding a crosslinking agent (Reference 4: Two-dimensional graphene oxide / MXene lamellar membrane cross-linked by urea with adjustable interlayer spacing for efficient dye rejection and ion sieving[J].Chemical Engineering Journal 480,148009(2024).). However, the reaction conditions of the above-mentioned regulation method are relatively harsh, the reaction process is complicated, and the MXene membrane is prone to swelling in water, resulting in poor stability. It cannot have both high dye / salt selectivity and high water permeability. Often when its water permeability is high, the dye / salt selectivity becomes poor.

[0005] For example, the water permeability of MXene / COFs membrane in reference 5 (MXene / COFs membrane with sandwich structure for rapid salt / dye separation by layer-by-layer electrophoretic deposition [J]. Journal of Membrane Science 704, 122857 (2024)) is 116.4 L / (m 2 ·h·bar), the dye retention rate is 99.5% (CR), the dye concentration is 100ppm, the NaCl retention rate is 1.1%, the Na2SO4 retention rate is 10.0%, the MgCl2 retention rate is 3.1%, and the MgSO4 retention rate is 4.9%.

[0006] The water permeability of TFN-1 membrane in reference 6 (Membranes with ZIF-8 regulated MXene nanosheet stacks for efficient molecular sieving [J]. Desalination 546, 116184 (2023)) is 40.8 L / (m 2 ·h·bar), the dye retention rate was 99.8% (CR), the dye concentration was 200ppm, the NaCl retention rate was 7.8%, and the MgSO4 retention rate was 5.9%.

[0007] The water permeability of MXC-3-L membrane in reference 7 (High performance mixed-dimensional assembled MXene composite membranes for molecular sieving [J]. Journal of Membrane Science 698, 122606 (2024).) is 55.1 L / (m 2 ·h·bar), the dye retention rate is 99.8% (CR), the dye concentration is 100ppm, the NaCl retention rate is 9.7%, and the Na2SO4 retention rate is 30.7%.

[0008] The water permeability of TFN-3 membrane in reference 8 (Hetero-dimensional 1D silk nanofibril and 2D MXene composite membrane with tailorable nanofluidic channels for enhanced water purification [J]. Journal of Membrane Science 697, 122517 (2024).) is 24.45 L / (m 2 ·h·bar), the dye retention rate was 99.43% (CR), the dye concentration was 200ppm, the NaCl retention rate was 3.9%, and the Na2SO4 retention rate was 14.4%.

[0009] The water permeability of (PEI / MXene)4 / TA / PES membrane in reference 9 (Nanofiltration membranes fabricated by plant polyphenol-intermediated MXene and polyethyleneimine layer-by-layer self-assembly for efficient dye / salt separation[J].Separation and Purification Technology 323,124343(2023).) is 204.0L / (m 2 ·h·bar), the dye retention rate was 99.9% (EB), the dye concentration was 10ppm, and the NaCl retention rate was 1.5%.

[0010] The water permeability of Fe(OH)3@GO membrane in reference 10 (In-situ nanoparticles intercalating graphene oxide membranes for superior water transport in dye desalination [J]. Journal of Membrane Science 697, 122544 (2024)) is 90.9 L / (m 2 ·h·bar), dye rejection rate was 99% (EB), dye concentration was 100ppm, and NaCl rejection rate was 4%.

[0011] The water permeability of rPGO-MXene membrane in reference 11 (Constructing reduced porous graphene oxide for tailoring mass-transfer channels in ultrathin MXene(Ti3C2Tx)membranes for efficient dye / saltseparation[J].Chemical Engineering Journal 457,141217(2023).) is 198.8L / (m 2 ·h·bar), dye retention rate is 100% (CR), dye concentration is 20ppm, NaCl retention rate is 5.3%, Na2SO4 retention rate is 7.5%, MgCl2 retention rate is 6%, and MgSO4 retention rate is 6.8%.

[0012] The water permeability of MXene / ZIF-L membrane in reference 12 (MXene / ZIF-L co-stacking membranes with high water permeation for solute-tailored selectivity. Applied Surface Science 625, 157194 (2023)) is 287.29 L / (m 2 ·h·bar), the dye retention rate is 99.2% (CR), the dye concentration is 50ppm, the NaCl retention rate is 4.45%, the Na2SO4 retention rate is 6.01%, and the MgCl2 retention rate is 1.58%.

[0013] The water permeability of CNT / MXene-PEI membrane in reference 13 (Electric field-assisted ultra-thin MXene conductive nanofiltration membrane for efficient dye / salt separation. Separation and Purification Technology 339, 126753 (2024)) is 156.11 L / (m 2 ·h·bar), the dye retention rate was 98.65% (CR), the dye concentration was 10ppm, and the Na2SO4 retention rate was 8.6%.

[0014] The water permeability of Pa / Terephthalaldehyde / DGC membrane in reference 14 (Development of novel ionic covalent organic frameworks composite nanofiltration membranes for dye / salt separation. Journal of Hazardous Materials 465, 133049 (2024)) is 68 L / (m 2 ·h·bar), dye retention rate is 97% (Rose Bengal), dye concentration is 5ppm, NaCl retention rate is 2.86%, Na2SO4 retention rate is 3.7%, MgCl2 retention rate is 6.96%, and MgSO4 retention rate is 4.98%.

[0015] Therefore, it is of great significance to study a method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation in order to solve the problems existing in the prior art. Summary of the invention

[0016] The purpose of the present invention is to solve the problems existing in the prior art and to provide a method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation.

[0017] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0018] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, wherein the MXene membrane is immersed in a mixed solution of tannic acid (TA) and 3-aminopropyltriethoxysilane (APTES) at room temperature (25°C), and TA and APTES will react chemically during the immersion process to obtain a MXene composite membrane for dye / salt separation. During the immersion process of the MXene membrane, TA and APTES will diffuse into the interlayer of the MXene membrane. The present invention introduces the chemical reaction between tannic acid and 3-aminopropyltriethoxysilane into the sub-nanometer space of the two-dimensional MXene membrane, and controls the growth of TA and APTES composite hydrophilic nanoparticles by regulating the concentration and time of TA and APTES, thereby achieving regulation of the interlayer spacing of the membrane. When the concentrations of TA and APTES are determined, the size of the hydrophilic nanoparticles between the sheets is controlled by controlling the immersion time. The longer the growth time, the larger the hydrophilic particles, and the larger the interlayer spacing of the supported membrane, thereby achieving continuous control of the interlayer spacing.

[0019] As the preferred technical solution:

[0020] The method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation as described above comprises the following specific steps:

[0021] (1) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution;

[0022] (2) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0023] (3) placing the dried MXene film in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane, soaking it at room temperature for 0.5 to 15 hours to obtain a wet MXene composite film, and then drying it at room temperature to obtain the MXene composite film.

[0024] In the method for preparing a MXene composite membrane for dye / salt separation as described above, the concentration of the tannic acid solution is 1.6 to 3.2 mg / mL, and the concentration of the 3-aminopropyltriethoxysilane solution is 0.5 to 2.5 mg / mL.

[0025] In the method for preparing a MXene composite membrane for dye / salt separation as described above, the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 0.01 to 100:1.

[0026] As described above, a method for preparing a MXene composite membrane for dye / salt separation, the preparation process of the MXene membrane is as follows:

[0027] (1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and hydrochloric acid, and the mixture was stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water, and then repeatedly centrifuged (3500 prm, 10 min) to remove the residual acid in the precipitate until the pH value of the solution reached 6.0, thereby obtaining a sample;

[0028] (2) The sample obtained in step (1) was dispersed in deionized water, and ultrasonically treated in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonication was centrifuged (8000 prm, 30 min) to remove the unpeeled flakes, and the supernatant was collected to obtain the MXene nanosheet solution;

[0029] (3) diluting the MXene nanosheet solution obtained in step (2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0030] (4) pouring the uniformly dispersed MXene solution obtained in step (3) into a filtration device equipped with a PES (polyethersulfone) substrate membrane and filtering to obtain a wet MXene membrane;

[0031] (5) The wet MXene film is placed in a constant temperature vacuum drying oven at 25 to 30°C for 8 to 16 hours to obtain a dry MXene film.

[0032] In the method for preparing a MXene composite membrane for dye / salt separation as described above, the concentration of hydrochloric acid in step (1) is 9 M, the ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6.

[0033] In the method for preparing a MXene composite membrane for dye / salt separation as described above, the concentration of the MXene nanosheet solution obtained in step (2) is 2.5 mg / mL.

[0034] In the method for preparing a MXene composite membrane for dye / salt separation as described above, the pore size of the PES substrate membrane in step (4) is 0.22 μm.

[0035] Beneficial effects:

[0036] (1) The present invention provides a method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, wherein the chemical reaction between tannic acid and 3-aminopropyltriethoxysilane is introduced into the sub-nanometer space of a two-dimensional MXene membrane, so that the interlayer spacing of the MXene membrane can be continuously regulated in a simple manner. Through the regulation, the MXene membrane can achieve efficient separation of dye / salt from salt ion interception while maintaining high water permeability.

[0037] (2) The present invention provides a method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation. The reaction conditions are milder, the preparation process is simple, the raw materials are readily available and are green and environmentally friendly. At the same time, the MXene composite membrane has a good effect on the separation of dye / salt mixtures. The preparation method has prospects for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Surface scanning electron microscope images and cross-sectional scanning electron microscope images of the MXene film and the MXene composite film in Example 7, wherein (a) a surface scanning electron microscope image of the MXene film, (b) a cross-sectional scanning electron microscope image of the MXene film, (c) a surface scanning electron microscope image of the MXene composite film, and (d) a cross-sectional scanning electron microscope image of the MXene composite film;

[0039] Figure 21 and 2. These are X-ray diffraction patterns of the MXene composite films in Examples 7 and 10 to 16 of the present invention. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0041] The test / calculation methods involved in the performance indicators of the present invention are as follows:

[0042] (1) Pure water permeability of MXene composite membrane:

[0043] The calculation formula of the permeability (J) of the MXene composite membrane is: J = V / (A×T×P), where V is the volume (L) of pure water permeated from the composite membrane within the time T (h), and A is the effective area of ​​the membrane (m 2 ), P is 1 (bar);

[0044] (2) Brilliant blue removal rate: The calculation formula for the Brilliant blue removal rate (r1) is: In the formula, C 01 is the concentration of the dye solution before filtration, C p1 is the concentration of the dye solution after filtration. Both were prepared using Thermo Fisher Scientific Evolution TM One UV-visible spectrophotometer was used to measure the

[0045] (3) Salt removal rate: The calculation formula for salt removal rate (r2) is: In the formula, C 02 is the concentration of the salt solution before filtration, C p2 is the concentration of the salt solution after filtration, both of which were measured using a Sartorius PB-10 pH meter.

[0046] (4) Scanning electron microscopy (SEM) test: A field emission scanning electron microscope (SU8010, Hitachi, Japan) was used to observe the surface and cross-section of the MXene film and MXene composite film.

[0047] (5) X-ray diffraction (XRD) test: X-ray diffractometer (Bruker D8, Germany) was used to analyze MXene films and MXene composite films.

[0048] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.

[0049] Example 1

[0050] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0051] (1) Preparation of MXene membrane:

[0052] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0053] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0054] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0055] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0056] (1.4) Pour 10 mL of the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0057] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0058] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2.4 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 0.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 4.8:1;

[0059] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0060] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 12 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0061] Example 2

[0062] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0063] (1) Preparation of MXene membrane:

[0064] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0065] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0066] (1.2) The sample obtained in step (1) was dispersed in deionized water, and ultrasonically treated in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonication was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0067] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0068] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0069] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0070] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2.4 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 2.4:1;

[0071] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0072] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 12 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0073] Example 3

[0074] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0075] (1) Preparation of MXene membrane:

[0076] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0077] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0078] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0079] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0080] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0081] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0082] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2.4 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.6:1;

[0083] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0084] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 12 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0085] Example 4

[0086] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0087] (1) Preparation of MXene membrane:

[0088] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0089] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0090] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0091] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0092] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0093] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0094] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2.4 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 2 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.2:1;

[0095] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0096] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 12 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0097] Example 5

[0098] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0099] (1) Preparation of MXene membrane:

[0100] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0101] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0102] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0103] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0104] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0105] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0106] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2.4 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 2.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 0.96:1;

[0107] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0108] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 12 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0109] Example 6

[0110] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0111] (1) Preparation of MXene membrane:

[0112] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0113] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0114] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0115] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0116] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0117] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0118] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 1.6 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.067:1;

[0119] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0120] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 12 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0121] Example 7

[0122] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0123] (1) Preparation of MXene membrane:

[0124] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0125] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0126] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0127] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0128] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0129] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0130] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.33:1;

[0131] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0132] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 12 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0133] from Figure 1 (a) shows that the surface of the MXene film is relatively flat. Figure 1 The cross-sectional view of the MXene film in (b) shows that its thickness is relatively thin, 50 nm; Figure 1 (c) shows that after the growth of hydrophilic nanoparticles, the surface of the MXene composite film has hydrophilic nanoparticles distributed, and Figure 1 (c) Cross-sectional view of MXene composite film. Compared with the cross-sectional view of MXene film, its thickness is obviously increased by 170 nm. The increase in film thickness indicates the growth of hydrophilic nanoparticles in the MXene film.

[0134] Example 8

[0135] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0136] (1) Preparation of MXene membrane:

[0137] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0138] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0139] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0140] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0141] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0142] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0143] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2.8 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.867:1;

[0144] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0145] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 12 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0146] Example 9

[0147] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0148] (1) Preparation of MXene membrane:

[0149] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0150] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0151] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0152] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0153] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0154] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0155] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 3.2 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 2.13:1;

[0156] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0157] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 12 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0158] Example 10

[0159] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0160] (1) Preparation of MXene membrane:

[0161] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0162] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0163] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0164] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0165] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0166] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0167] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.333:1;

[0168] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0169] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 0.5 h, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0170] Embodiment 11

[0171] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0172] (1) Preparation of MXene membrane:

[0173] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0174] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0175] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0176] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0177] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0178] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0179] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.333:1;

[0180] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0181] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 4 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0182] Example 12

[0183] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0184] (1) Preparation of MXene membrane:

[0185] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0186] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0187] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0188] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0189] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0190] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0191] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.333:1;

[0192] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0193] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 4.5 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0194] Example 13

[0195] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0196] (1) Preparation of MXene membrane:

[0197] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0198] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0199] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0200] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0201] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0202] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0203] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.333:1;

[0204] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0205] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 5 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0206] Embodiment 14

[0207] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0208] (1) Preparation of MXene membrane:

[0209] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0210] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0211] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0212] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0213] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0214] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0215] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.333:1;

[0216] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0217] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 6 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0218] Embodiment 15

[0219] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0220] (1) Preparation of MXene membrane:

[0221] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0222] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0223] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0224] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0225] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0226] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0227] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.333:1;

[0228] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0229] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 9 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0230] Example 16

[0231] A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, the specific steps are as follows:

[0232] (1) Preparation of MXene membrane:

[0233] (1.1) MAX (Ti3AlC2) was added to an etching solution obtained by mixing LiF and 9M hydrochloric acid for 15 min, and stirred continuously at 40°C for 24 h. After the reaction was completed, the collected precipitate was repeatedly washed with deionized water until the pH value of the solution was 6.0, thereby obtaining a sample;

[0234] The ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.6;

[0235] (1.2) The sample obtained in step (1.1) was dispersed in deionized water, and subjected to ultrasonic treatment in an ice bath for 1 h in a nitrogen atmosphere. The suspension obtained by ultrasonic treatment was centrifuged and the supernatant was collected to obtain a MXene nanosheet solution with a concentration of 2.5 mg / mL;

[0236] (1.3) diluting the MXene nanosheet solution obtained in step (1.2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution;

[0237] (1.4) Pour the uniformly dispersed MXene solution obtained in step (1.3) into a filtration device equipped with a PES substrate membrane with a pore size of 0.22 μm to obtain a wet MXene membrane;

[0238] (1.5) The wet MXene film was placed in a constant temperature vacuum drying oven at 25 °C for 12 h to obtain a dry MXene film.

[0239] (2) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution with a concentration of 2 mg / mL, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 1.5 mg / mL; the mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 1.333:1;

[0240] (3) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane;

[0241] (4) The dried MXene film obtained in step (1) is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane obtained in step (3), immersed at room temperature for 15 hours, and dried at room temperature to obtain a MXene composite film for dye / salt separation.

[0242] Table 1 is based on Figure 2 The X-ray diffraction results are calculated by the Bragg equation 2dsinθ=nλ to obtain the corresponding interplanar spacing; where d is the interplanar spacing; n is the reflection order; θ is the grazing angle; and λ is the wavelength of the X-ray. It can be seen that the MXene composite film prepared by the present invention can achieve continuous regulation of the interlayer spacing of the MXene film by adjusting the growth time of its hydrophilic nanoparticles.

[0243] Table 1

[0244]

[0245]

[0246] Table 2

[0247]

[0248] Table 2 shows the separation performance of the MXene composite membranes prepared in Examples 1 to 16. It can be seen from Table 2 that the preparation method of the MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation proposed in the present invention can achieve good retention performance for dye molecules by regulating the obtained MXene composite membrane, while having good permeability to inorganic salts, good dye / salt selectivity, and the composite membrane has good pure water permeability. After comparison of different embodiments, the MXene / TA-2-AP-1.5-12 (Example 7) composite membrane has good water permeability (water permeability is 317L / (m 2 ·h·bar)) with excellent performance, while taking into account the good performance of dye / salt separation, the retention rate of brilliant blue is 97.54%, the retention rate of NaCl is 3.10%, the retention rate of MgCl2 is 4.28%, the retention rate of Na2SO4 is 5.76%, and the retention rate of MgSO4 is 6.96%.

Claims

1. A method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation, characterized in that: The MXene membrane was immersed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane at room temperature to prepare a MXene composite membrane for dye / salt separation.

2. The method for preparing a MXene composite membrane with continuously adjustable interlayer spacing for dye / salt separation according to claim 1, characterized in that: The specific steps are as follows: (1) dissolving tannic acid in a Tris-HCl solution at pH=8.5 to obtain a tannic acid solution, and dissolving 3-aminopropyltriethoxysilane in anhydrous ethanol to obtain a 3-aminopropyltriethoxysilane solution; (2) mixing the tannic acid solution and the 3-aminopropyltriethoxysilane solution at room temperature and stirring to obtain a mixed solution of tannic acid and 3-aminopropyltriethoxysilane; (3) The dried MXene film is placed in a mixed solution of tannic acid and 3-aminopropyltriethoxysilane, immersed at room temperature for 0.5 to 15 hours, and dried at room temperature to obtain the MXene composite film.

3. The method for preparing a MXene composite membrane for dye / salt separation according to claim 2, characterized in that: The concentration of the tannic acid solution is 1.6-3.2 mg / mL, and the concentration of the 3-aminopropyltriethoxysilane solution is 0.5-2.5 mg / mL.

4. The method for preparing a MXene composite membrane for dye / salt separation according to claim 3, characterized in that: The mass ratio of tannic acid to 3-aminopropyltriethoxysilane is 0.01-100:

1.

5. The method for preparing a MXene composite membrane for dye / salt separation according to claim 2, characterized in that: The preparation process of MXene film is as follows: (1) adding MAX to an etching solution obtained by mixing LiF and hydrochloric acid, stirring continuously at 40° C. for 24 h, and after the reaction is completed, repeatedly washing the collected precipitate with deionized water until the pH value of the solution is 6.0, thereby obtaining a sample; (2) dispersing the sample obtained in step (1) in deionized water, ultrasonically treating in an ice bath for 1 h in a nitrogen atmosphere, centrifuging the suspension obtained by ultrasonication, and collecting the supernatant, which is the MXene nanosheet solution; (3) diluting the MXene nanosheet solution obtained in step (2) to 0.004 mg / mL and ultrasonicating at room temperature for 15 min to obtain a uniformly dispersed MXene solution; (4) pouring the uniformly dispersed MXene solution obtained in step (3) into a filtration device equipped with a PES substrate membrane and filtering to obtain a wet MXene membrane; (5) The wet MXene film is placed in a constant temperature vacuum drying oven at 25 to 30°C for 8 to 16 hours to obtain a dry MXene film.

6. The method for preparing a MXene composite membrane for dye / salt separation according to claim 5, characterized in that: In step (1), the concentration of hydrochloric acid is 9 M, the ratio of LiF to hydrochloric acid is 0.8 g:10 mL, and the mass ratio of MAX to LiF is 1:1.

6.

7. The method for preparing a MXene composite membrane for dye / salt separation according to claim 5, characterized in that: The concentration of the MXene nanosheet solution obtained in step (2) is 2.5 mg / mL.

8. The method for preparing a MXene composite membrane for dye / salt separation according to claim 5, characterized in that: The pore size of the PES substrate membrane in step (4) is 0.22 μm.